Luciferase reporter mycobacteriophage (TM4:: GeNL ) enables rapid assessment of drug susceptibilities and inducible macrolide resistance in Mycobacterium abscessus complex - Rajagopalan, Saranathan; Das, Lahari; Kohlerschmidt, Donna J.; Rourke, Amy K.; Shakir, Salika M.; Larsen, Michelle H.; O’Donnell, Max R.; Szymczak, Wendy A.; Escuyer, Vincent E.; Thwe, Phyu M.; Jacobs, William R. (Journal of clinical microbiology, 2025)
Mycobacterium abscessus (MAB) is a notorious human pathogen causing severe infections in individuals with cystic fibrosis and immunocompromised patients. Treatment options for MAB are very limited as they are resistant to multiple drugs through intrinsic and acquired resistance mechanisms. While macrolides and amikacin are the key drugs in the fight against MAB infections, emerging drug resistance is compromising their efficacy. Current growth-based drug susceptibility testing (DST) method takes 7 to 14 days to identify clarithromycin susceptibility due to the presence of inducible macrolide resistance and 3 to 5 days for other drugs. We developed a novel luciferase reporter mycobacteriophage (LRM) based phenotypic DST method using TM4:: GeNL to assess MAB drug susceptibility based on metabolic inhibition rather than growth. LRM-DST significantly reduces the DST turnaround time to 48 h and provides rapid assessment of MAB susceptibility to drugs, including inducible macrolide resistance, thereby accelerating the treatment process and improving patient outcomes.